Mathematics Learning Media to Enhance Students’ Mathematical Literacy - Annisa Aurelia Salsabila; Masrukan; Zaenuri; Walid (Media Pendidikan Matematika, 2025)
Mathematical ability is considered essential and plays a significant role in helping students solve problems in their daily lives. One important component of mathematical ability is mathematical literacy, which refers to an individual's capacity to formulate, use, and interpret mathematics in various real-world contexts. However, many students still struggle to apply mathematical concepts to everyday situations. Therefore, a learning approach that enhances students’ mathematical literacy is needed, including the use of appropriate learning media. This study employed a systematic literature review of experimental and developmental studies to examine mathematics learning media that enhance students’ mathematical literacy. The reviewed literature consisted of national and international journal articles indexed in SINTA and Scopus, published between 2015 and 2025, with students as the research subjects. The results of this study indicate that learning media such as Virtual Mathematics Kits, GeoGebra, Wingeom, Scratch, Wordwall, Kahoot, e-modules, e-LKPD, mathematics comics, Math City Map, and the selection of appropriate learning models are consistently effective in improving students’ mathematical literacy. Digital and interactive media enhance mathematical literacy through visualization, interactivity, and dynamic exploration of mathematical concepts, while contextual and non-digital media strengthen students’ abilities to formulate, employ, and interpret mathematics through real-life problem-solving and meaningful learning experiences across educational levels.